Diurnal changes in the perception of emotions in music: Does the time of day matter?. (September 2014) - Brabant, Olivier; Toiviainen, Petri
According to the Hindustani music tradition, the ability of a song to induce certain emotions depends on the time of day: playing a song at the right time is said to maximise its emotional effect. The present exploratory study investigated this claim by combining findings in chronobiology, mood research and music perception. It has already been established that some aspects of our mood fluctuations follow a cyclical pattern. Besides, it is a known fact that our current mood influences our perception and assessment of emotions. However, these elements have never been linked together in a study examining the effect of mood cyclicity on perceived emotions in music. To test the hypothesis of a link between the two, Western film music excerpts were played to 36 participants at two different times (9 a.m. and 4 p.m.). Their task was to rate the perceived emotional content of each clip. The results showed that sad and tender clips were rated higher on sadness and tenderness in the morning compared to the afternoon. Furthermore, the more tired the participants were in the afternoon, the higher was their perception of fear in angry and fearful music. Although the reported effect sizes were small, these findings could have important implications for ethnomusicologists, emotion researchers and music therapists.